THE FIGURE OF A TEACHER IN THE PERSPECTIVES OF ZAKIAH DARADJAT AND AL-GHAZALI (A COMPARATIVE STUDY) - Ali, Nur; Faisol, Achmad; Al Ghafir, Abu Aman Siddiq; Supriatno, Djoko; Winarni, Sri (Program Studi Pendidikan Agama Islam, 2025)
Education has been a fundamental concern and a top priority since the earliest stages of human life. In Islam, the importance of education is deeply rooted, as reflected in the prophetic tradition emphasizing lifelong learning from the womb to the grave. This study aims to compare the educational perspectives of two prominent Muslim scholars, Al-Ghazali and Zakiah Daradjat, particularly regarding the ideal characteristics of a teacher. The research seeks to identify similarities and differences in their views and evaluate their relevance as references for contemporary educators. This qualitative study employs historical and philosophical approaches, utilizing inductive-deductive, comparative, and descriptive methods of analysis. The findings reveal that both Al-Ghazali and Zakiah Daradjat have made significant intellectual contributions to the conceptualization of the teacher's role. While sharing many foundational principles, their perspectives also exhibit distinct differences shaped by their respective historical and cultural contexts. Operationally, their concepts remain applicable and offer valuable insights for modern educators, provided they are adapted to current pedagogical frameworks and enriched through contemporary educational strategies.